Impact of process and device dimensions on Bio-TFET Sensitivity - Macambira, C. N.; Agopian, P. G. D. [UNESP]; Martino, J. A.; IEEE (Ieee, 2018)
This paper reports the impact of process and dimensions on the sensitivity of the double gate Bio-TFET for drain and source underlap structures. The Bio-TFET is simulated using different dielectric permittivity materials (epsilon) localized over the drain to gate and gate to source underlap regions. The impact of silicon thickness (t(Si)), gate oxide (t(ox)), underlap length at the source (L-US) and at the drain region (L-UD) were studied. The best sensitivity for Bio-TFET biosensor is obtained for the source underlap (L-US) of 25 nm, channel silicon thickness of 5 nm and gate oxide thickness of 3 nm. The energy band diagram and the band-to-band tunneling generation rate were used to explain the results.
Keywords: TFET; Biosensor; Bio-TFET; Tunnel-FET